Real Coded Genetic Algorithm Based Improvement of Efficiency in Interleaved Boost Converter - M Arundevi; K Valarmathi; R Mahendran (Institute of Advanced Engineering and Science, 2015)
The reliability, efficiency, and controllability of Photo Voltaic power systems can be increased by embedding the components of a Boost Converter. Currently, the converter technology overcomes the main problems of manufacturing cost, efficiency and mass production. Issue to limit the life span of a Photo Voltaic inverter is the huge electrolytic capacitor across the Direct Current bus for energy decoupling. This paper presents a two-phase interleaved boost converter which ensures 180 angle phase shift between the two interleaved converters. The Proportional Integral controller is used to reshape that the controller attempts to minimize the error by adjusting the control inputs and also real coded genetic algorithm is proposed for tuning of controlling parameters of Proportional Integral controller. The real coded genetic algorithm is applied in the Interleaved Boost Converter with Advanced Pulse Width Modulation Techniques for improving the results of efficiency and reduction of ripple current. Simulation results illustrate the improvement of efficiency and the diminution of ripple current.